Pajak Penghasilan Orang Pribadi Pelaku E-Commerce Di Singaraja - Putu Arya Wahyu Prebawa; I Gede Komang Chahya Bayu Anta Kusuma (Politeknik Keuangan Negara STAN, 2022)
Online transactions in Indonesia continue to grow every year, in 2020 e-commerce transactions grew 23.11% yoy. Dominated by young consumers with the fashion and beauty products dominated the transaction. This increase causes the tax potential of e-commerce transactions to increase. In Bali, through webscraping in Shopee and Tokopedia, there are 1,244 stores that has gross sales at least 50 million rupiah per month. This study aims to determine tax compliance, business processes, and the obstacles faced by individual taxpayers in fulfilling their tax obligations. This study limits the scope of the research in Singaraja City, Buleleng Regency, Bali Province. This study uses qualitative approach with primary data sources consisting of interview and observation methods, this study also use secondary data through literature studies and data from DJP. The conclusion of this study is the compliance of individual taxpayers at KPP Pratama Singaraja is quite low, with business processes that can be divided into two category, namely retail entrepreneurs and independent production. This low level of tax compliance caused by weak coercion to fulfill tax obligations, lack of understanding, and bad perceptions of taxes.